Les anciens vignobles « ornements des villes » : legs, images, opportunités, perspectives - Jean-Pierre Husson (Projets de Paysage)
Cities used to be sourrounded by small tracts of vineyards, orchards, garden, in addition to vast estates and meadows. This landscape environment was partly overlaid by urban sprawl but sometimes goes through a kind of renaissance. It is now contemplated as part of the urban green infrastructure and urban cultural heritage. It can be accounted for again through a new city governance.